Analysis of 3-D body measurements to determine trousers sizes of military combat clothing - Traumann, Ada (Array, 2019)
The aim of this paper was to analyse several measurements of soldiers to provide a reference for trousers sizes of military combat clothing. For sizing and fitting of military clothing, information on the body measurements of the user population is a precondition. More than 400 soldiers in the Estonian and Latvian Defence Forces as well as the military personnel were measured using Human Solution 3-D scanner. It focused on collating basic human body measurement data for the revision of size charts by STANAG 2335. Fit and comfort of trousers mainly relate to the following measurements: waist girth, leg inseam, leg length, and waistband. Present parameters play a significant role in the quality of trousers to ensure the wearer’s mobility in all situations particularly concerning the activities of soldiers. Correlating measurements and existing sizing systems are made to offer recommendations for manufacturers. In addition, this paper helps to provide sizing and fitting criteria of military combat clothing to STANREC document compiled by NATO RTO HFM-266 Group.